What Counts as Care? Structural Critique of Digital Health Models - Wang, Xi; Yang, Fuwen; Trafford, Julie; Qiu, Wuqi; Conn, Cath (SAGE Publishing, 2026)
In a world increasingly saturated with digital health technologies, the promise of empowerment through information has become almost axiomatic. Yet what if access does not equate to understanding, and what if the sleek interfaces and personalized nudges of today's tools merely simulate agency while displacing it? This presentation interrogates the epistemological and ethical limits of four dominant models underpinning digital health design: the information deficit model, the knowledge–attitude–practice (KAP) framework, health literacy strategies, and behavioral nudging. Despite their differences, each presumes a rational, autonomous user who simply needs the right data or design to act wisely. Drawing on critical public health literature and sociotechnical theory, we argue that these frameworks obscure the structural and social determinants of health (SDoH), such as time poverty, financial stress, and cultural tensions, that fundamentally constrain genuine agency. Rather than merely optimizing individual behavior, this commentary compels the field to confront fundamental questions of power: Who gets to define health? Who designs the algorithm? And who is excluded in the process? By centering these inquiries, the real frontier is not smarter apps, but fairer governance. The paper concludes that addressing the digital divide requires structural interventions, such as participatory oversight and redistributive design, ensuring that digital health systems are grounded in human understanding rather than just administrative efficiency.
Keywords: 420302 Digital health; Digital health; health communication; health literacy; technology and governance; 4203 Health Services and Systems; 42 Health Sciences; Social Determinants of Health; Behavioral and Social Science; Health Disparities; Health Disparities and Racial or Ethnic Minority Health Research; Generic health relevance; 3 Good Health and Well Being; 4203 Health services and systems